A new bone adhesive candidate- does it work in human bone? An ex-vivo preclinical evaluation in fresh human osteoporotic femoral head bone. Issue 6 (June 2022) - Bojan, Alicja J.; Stadelmann, Vincent A.; Wu, Dan; Pujari-Palmer, Michael; Insley, Gerard; Sundh, Daniel; Persson, Cecilia; Engqvist, Håkan; Procter, Philip
Highlights: The study is a first pre-clinical interpretation of possible indications for a bone adhesive such as fixating of small intraarticular fragments A new mechanical testing model was developed to evaluate the bone adhesive in human femoral head bone freshly harvested at surgery The bone cores were successfully glued and substantial bonding strength was maintained at both 2 and 24 hours after gluing Abstract: Introduction: The fixation of small intraarticular bone fragments is clinically challenging and an obvious first orthopaedic indication for an effective bone adhesive. In the present study the feasibility of bonding freshly harvested human trabecular bone with OsStic R, a novel phosphoserine modified cement, was evaluated using a bone cylinder model pull-out test and compared with a commercial fibrin tissue adhesive. Methods: Femoral heads (n=13) were collected from hip fracture patients undergoing arthroplasty and stored refrigerated overnight in saline medium prior to testing. Cylindrical bone cores with a pre-inserted bone screw, were prepared using a coring tool. Each core was removed and glued back in place with either the bone adhesive (α-tricalcium phosphate, phosphoserine and 20% trisodium citrate solution) or the fibrin glue. All glued bones were stored in bone medium at 37°C. Tensile loading, using a universal testing machine (5 kN load cell), was applied to each core/head. For the bone adhesive, bone cores were tested at 2 (n=13) and 24 (n=11) hours. For the fibrin tissue adhesive control group (n=9), bone cores were tested exclusively at 2 hours. The femoral bone quality was evaluated with micro-CT. Results: The ultimate pull-out load for the bone adhesive at 2 hours ranged from 36 to 171 N (mean 94 N, SD 42 N). At 24 hours the pull-out strength was similar, 47 to 198 N (mean 123 N, SD 43 N). The adhesive failure usually occurred through the adhesive layer, however in two samples, at 167 N and 198 N the screw pulled out of the bone core. The fibrin tissue adhesive group reached a peak force of 8 N maximally at 2 hours (range 2.8-8 N, mean 5.4 N, SD 1.6 N). The mean BV/TV for femoral heads was 0.15 and indicates poor bone quality. Conclusion: The bone adhesive successfully glued wet and fatty tissue of osteoporotic human bone cores. The mean ultimate pull-out force of 123 N at 24 hours corresponds to ∼ 300 kPa shear stress acting on the bone core. These first ex-vivo results in human bone are a promising step toward potential clinical application in osteochondral fragment fixation.